Advances in Occupational Health in Guatemala - M. E. González Alvarez (Ubiquity Press, 2018)
Occupational health in Guatemala has come a long way. In 1958, the first Regulation of Occupational Health by the Guatemalan Social Security Institute was published. There wasn´t another Directive in the country regarding this issue until the year 2000, when the National Council for Occupational Safety and Health was created. In 2014, it published the Governmental Agreement 229-2014 Occupational Health and Safety Regulations, which came into force on September 8th, 2015. Nowadays there are other institutions that care about this topic. Some of these institutions promote occupational health training through courses, workshops, seminars, etc., but there is not a formal education program yet. There are some other institutions, such as the National Institute of Statistics, which generates information concerning employment, unemployment, characteristics, composition, structure, and functioning of the labor market through surveys. And finally, there are other institutions like the Health, Labor and Environment Program of Central America SALTRA, which promotes investigation in this topic, generates information as well as endorses training regarding occupational safety as an important issue in the country.